Modelling Abbreviation in Internet Slang: a Comparison Study of Indonesian Internet Slang and English Internet Slang - Eline Rozaliya Winarto (Universitas PGRI Semarang, 2019)
People, all around the world, use internet recently. The usage of internet changes the language usage as well. People tend to use short word thus they are abbreviating some words or phrases. Many of new words are coined lately because of the using of internet. The formation of the new word then belongs to the study of morphology. The main theory of this research is morphology. Moreover, it uses the theory of abbreviation. Some types of abbreviation such as blends, acronym, alphabetism and clipping are found in this research.This research entitled ‘Modelling Abbreviation in Internet Slang: A Comparison Study of Indonesian Internet Slang and English Internet Slang’. The data are taken from some websites which have internet slang dictionary. The writer only took 20 data for this research from those online internet slang dictionaries. There are ten (10) data for English Internet slang language and ten (10) data for Indonesian internet slang language. Conducting the analysis, the writer revealed that the process of abbreviation in English internet slang language is as follow: Blends (1): swexy; Acronym (2): Afair, Mapoti; Alphabetism (2): BTW, FYI; and Clipping (2): acc, app. Meanwhile, the result of abbreviation process in Indonesian internet slang language is as follow: Blends (3): gaptek, jones, palbis; Acronym (3): bais, ucul, woles; Alphabetism (2): PHP, SMS; and Clipping (2): krik, cus.